(untitled) (Orfeu, 2021)
This article presents musical creation in open musical pedagogies, providing an overview of the theme. We will bring, in the first part, a historical and conceptual characterization of how such pedagogies were being forged. In this sense, it is worth pointing out the landmark of the creation of the Foro Latinoamericano de Educación Musical (FLADEM), which became the space for debate on such pedagogies. Next, we will speak about the perspective of creativity/musical creation and how it was built, mainly from the ideas of Violeta Hemsy de Gainza. In the third part we will speak about the formation, acting and evaluation in creative practices in music education. Finally, we will present some creative proposals from authors guided by open pedagogies based on three axes: musical experiences centered on practice, participatory musical praxis and integrated musical praxis. In the final considerations, we will comment about the conceptual expansion of open pedagogies and the emergence of new issues for music education.